2005
DOI: 10.1111/j.1346-8138.2005.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Extramammary Paget's Disease/Carcinoma Successfully Treated with a Combination Chemotherapy: Report of Two Cases

Abstract: We have treated two patients with extramammary Paget's disease/carcinoma (EMPD/C), a 62-year-old woman and a 78-year-old man. In both patients, lymph nodes in the areas of the bilateral inguinal, external iliac arteries, and abdominal aorta were affected. After surgery, they underwent 5 courses of systemic combination chemotherapy at 4-week intervals to residual or recurrent lymph node metastasis. Each course consisted of 3.5 mg mitomycin C and 50 mg epirubicin (day 1), 0.6 mg vincristine (days 1 and 7), 30 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 6 publications
0
23
0
4
Order By: Relevance
“…Eine Auswertung der Literatur von 1990 bis 2008 ergibt, dass die primäre kutane Erkrankung, die nicht mit anderen Neoplasien assoziiert war, 58% der Fälle darstellt [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41], während 10% der EMPD-Fälle im Zusammenhang mit synchroner oder metachroner Neoplasie standen [10,12,21,32,35]; 1% war mit einem Adnexkarzinom assoziiert [21,41]; in 28% der Fälle lag eine intraepidermale Streuung eines Rektumkarzinoms (pagetoides Phänomen) vor [7,10,11,19,21,…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…Eine Auswertung der Literatur von 1990 bis 2008 ergibt, dass die primäre kutane Erkrankung, die nicht mit anderen Neoplasien assoziiert war, 58% der Fälle darstellt [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41], während 10% der EMPD-Fälle im Zusammenhang mit synchroner oder metachroner Neoplasie standen [10,12,21,32,35]; 1% war mit einem Adnexkarzinom assoziiert [21,41]; in 28% der Fälle lag eine intraepidermale Streuung eines Rektumkarzinoms (pagetoides Phänomen) vor [7,10,11,19,21,…”
Section: Diskussionunclassified
“…Die Auswertung der Literatur von 1990 bis 2008 ergab 193 Fälle eines perianalen EMPD, 112 Fälle waren intraepithelial oder erstreckten sich bis zur Dermis [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 …”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Tumour responses have been reported with combination chemotherapy such as mitomycin C 3.5 mg/m 2 and epirubicin 50 mg/m 2 (day 1), vincristine 6 mg/m 2 (days 1 and 7), cisplatin 30 mg/m 2 (days 1-3), and 5-fluorouracil 350 mg/m 2 (days 3-7), with pr and complete response [58][59][60] . The literature also describes prs with 5-fluorouracil plus cisplatin 61 in a low-dose schedule (5-fluorouracil 500 mg daily, 7 days per week, and cisplatin 5 mg daily, 5 days per week), followed by oral tegafur uracil (600 mg daily) 62 .…”
Section: 24mentioning
confidence: 99%
“…[1][2][3] The treatment of penoscrotal EMPD includes surgical excision, chemotherapy, radiotherapy, laser treatment and imiquimod cream. [4][5][6][7][8] However, local wide excision and immediate reconstruction is the preferred treatment of Chinese urologists. [9][10][11] Our experience with 130 patients evaluated at mid-term follow-up demonstrated that intraoperative frozen-section biopsy was a reliable means to detect invisible tumours and could significantly reduce recurrence.…”
Section: Introductionmentioning
confidence: 99%